Identifying Flexible Pool Pumps Suitable for Distributed Demand Response Schemes. (August 2019) - Andrew, Lachlan L H; Pop, Draga Doncila; Razzaghi, Reza; Dowe, David L
Abstract: Demand response will be an important tool as non-dispatchable generation is added to the grid. Swimming pool filtration pumps are a promising appliance for the grid operator to control because, unlike air conditioners, their time of operation can be shifted by a day without affecting their primary role. Although many customers set and forget the timer settings, this paper studies smart meter data and demonstrates that many change the settings frequently. A "care index" is proposed that quantifies how much a customer appears to care about the precise timing of pump operation, which indicates how willing they are likely to be to relinquish control to the grid operator.